An Investigation on the Fibrin Glue’s Impact on Myringoplasty’s Success Rate: A Randomized Controlled Study - Ahsan Qureshi, Nisar Akber Khan, Muhammad Saleem, Ramzan Ali, Sultan Badar Munir, Ali Husnain Sheikh, Khurram Shahzad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study’s goal is to evaluate the success rates of graft uptake in platelet-rich fibrin-assisted underlay myringoplasties employing temporalis fascia grafts to those in traditional underlay myringoplasties. Methods: This study was conducted in Mayo Hospital in Lahore’s ENT department carried out this double-blind, randomized, controlled trial investigation. We recruited 60 individuals with dry central tympanic membrane perforations. Patients with co-morbidities such as diabetes and sensorineural hearing loss were not included. Probability basic random sampling was used. The patients were split into two groups using a lottery system. With the help of SPSS version 26, statistical analysis was carried out. The P-value was calculated using the chi-square test. Results: There were 60 patients, of whom 38 were males and 22 were women. The control group’s average age was 27.53 ± 11.41 years, but the study group’s average age (Fibrin) was 31.77 ± 12.43 years. At the 2-month follow-up, the grafts were successfully absorbed by every patient in the platelet-rich fibrin group. 23 out of 30 patients in the control group who underwent the conventional method successfully absorbed their grafts, however, the remaining 7 patients had different issues that led to graft rejection. Practical Implication: The tympanic membrane would mend more quickly if platelet-rich fibrin was used after ear procedures. Fibrin glue in tympanoplasty has been tried in several locations throughout the globe. [7,8] When concentrated fibrinogen solutions are combined with thrombin, fibrin glue is created. It may also be made from platelet-rich plasma. Our research compares platelet-rich fibrin-assisted underlay myringoplasties employing temporalis fascia grafts to traditional underlay myringoplasties to see which has a higher graft uptake success rate. Conclusions: The use of platelet-rich fibrin on the anterior ligament grafting line and perforation edges during underlay myringoplasty has greatly increased the success rate of the graft. Keywords: platelet-rich fibrin, temporal fascia graft, myringoplasty